SEDIMENTOLOGY AND STRATIGRAPHY OF THE KUDAT FORMATION (OLIGOCENE- EARLY MIOCENE), KUDAT PENINSULA, SABAH - ABDUL JALIL, NURSYAZWANI (2016)
A detailed study of sedimentology and stratigraphy of the Kudat Formation (Oligocene - Early Miocene), Sabah, Malaysia was undertaken to: (1) describe and interpret the different sedimentary facies, (2) evaluate the facies associations in terms of sedimentary processes and environments, and (3) construct a depositional model taking into account the sedimentology and biostratigraphy of the Kudat Formation. This study was conducted on ten outcrops of the Kudat Peninsula. Seven facies (Fl- F7) have been identified: structureless/massive sandstone (Fl), parallel laminated sandstone (F2), parallel laminated and rippled sandstone (F3), rippled sandstone (F4), graded bedded sandstone (F5), chaotic deposits (F6) and parallel laminated to structureless mudstone and siltstone (F7). The facies resulted in recognition of three facies associations: upper submarine fan (FA1), middle submarine fan (FA2) and lower submarine fan (FA3).